Tanggung Jawab Notaris Dalam Penyusunan Akta Otentik Dan Dampaknya Terhadap Kepastian Hukum Serta Etika Profesi Di Indonesia: TANGGUNG JAWAB NOTARIS DALAM PENYUSUNAN AKTA OTENTIK DAN DAMPAKNYA TERHADAP KEPASTIAN HUKUM SERTA ETIKA PROFESI DI INDONESIA - Huda, Miftakhul; Muthi'ah Mairo, Putri (Jurnal Media Justitia Nusantara, 2025)
The deed made by a notary is referred to as an authentic deed, which is stronger as compared to the deed under hand. This authentic deed serves as a legal proof tool before the court and is an important basis in various legal transactions. The purpose of this study is to analyze the responsibility of notaries in the preparation of authentic deeds, explore their impact on legal certaintyThis research uses a qualitative approach with a descriptive method, which aims to explore and describe the role of notaries in the preparation of authentic deeds, as well as its impact on legal certainty and professional ethics in Indonesia. The results of this study show that the responsibility of notaries in the preparation of authentic deeds has a significant impact on legal certainty in Indonesia. Deeds prepared by a notary must meet strict legal standards, and any errors in the drafting process can harm the parties involved, both materially and legally. Although notaries are aware of the importance of their role, there are still major challenges related to external pressures, high workloads, and a lack of adequate supervision in the profession. Data shows that 40% of notaries feel pressured to meet client requests that are contrary to regulations, while 30% reveal time constraints as a major factor in reducing the thoroughness of drafting authentic deeds. The data also shows that although the professional code of ethics already exists, its implementation in the field is still less than optimal, with 35% of notaries feeling that they do not receive support from professional associations in the form of continuous training. In addition, the use of digital technology in the preparation of deeds also presents new challenges for notaries, where 45% of notaries admitted that they feel unprepared to face it.